2023
DOI: 10.3390/microorganisms11040957
|View full text |Cite
|
Sign up to set email alerts
|

Purified Plant-Derived Phenolic Acids Inhibit Salmonella Typhimurium without Alteration of Microbiota in a Simulated Chicken Cecum Condition

Abstract: Salmonella enterica serovar Typhimurium (ST) remains a predominant zoonotic pathogen because of its colonization in poultry, survivability in the environment, and increasing antibiotic-resistance pattern. Plant-derived phenolics, gallic acid (GA), protocatechuic acid (PA), and vanillic acids (VA) have demonstrated antimicrobial activity in vitro; therefore, this study collected chicken cecal fluid and supplemented it with these phenolics to evaluate their potential for eliminating ST and mod-ulating the microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…As mentioned before, though the GI tract is a complex ecosystem with many variables that can affect the efficacy of an antimicrobial product, cell monolayers have long been used as models for studying host-pathogen interactions between bacteria and eukaryotic cells [ 38 ]. One of the factors that affects the potency of phenolic acids is pH, which has been shown in the past to either increase their antimicrobial effect or neutralize them [ 39 ]. The initial antimicrobial assay performed in DMEM with 10% FBS showed that inhibitory potential increased with concentration in the case of PA and VA, though they required high doses in order to inhibit ST to undetectable levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned before, though the GI tract is a complex ecosystem with many variables that can affect the efficacy of an antimicrobial product, cell monolayers have long been used as models for studying host-pathogen interactions between bacteria and eukaryotic cells [ 38 ]. One of the factors that affects the potency of phenolic acids is pH, which has been shown in the past to either increase their antimicrobial effect or neutralize them [ 39 ]. The initial antimicrobial assay performed in DMEM with 10% FBS showed that inhibitory potential increased with concentration in the case of PA and VA, though they required high doses in order to inhibit ST to undetectable levels.…”
Section: Discussionmentioning
confidence: 99%
“…To determine changes in the antimicrobial efficacy of phenolic acid under various pH ranges within DMEM, increasing concentrations of phenolic acids within DMEM were adjusted to a pH between 3 and 10 and tested for inhibition of ST, as has been described previously with some modifications [ 39 ]. Briefly, aliquots of DMEM were either independently supplemented with increasing concentrations of GA, PA, and VA ranging from 0.0625 to 5.0 mg/mL or left untreated as the control lacking phenolic acids.…”
Section: Methodsmentioning
confidence: 99%